Nicastrin is required for amyloid precursor protein (APP) but not Notch processing, while anterior pharynx‐defective 1 is dispensable for processing of both APP and Notch. Issue 6 (17th January 2016) - Hu, Chen; Zeng, Linlin; Li, Ting; Meyer, Michael A.; Cui, Mei‐Zhen; Xu, Xuemin
Abstract: The γ‐secretase complex is composed of at least four components: presenilin 1 or presenilin‐2, nicastrin (NCT), anterior pharynx‐defective 1 (Aph‐1), and presenilin enhancer 2. In this study, using knockout cell lines, our data demonstrated that knockout of NCT, as well as knockout of presenilin enhancer 2, completely blocked γ‐secretase‐catalyzed processing of C‐terminal fragment (CTF)α and CTFβ, the C‐terminal fragments of β‐amyloid precursor protein (APP) produced by α‐secretase and β‐secretase cleavages, respectively. Interestingly, in Aph‐1‐knockout cells, CTFα and CTFβ were still processed by γ‐secretase, indicating Aph‐1 is dispensable for APP processing. Furthermore, our results indicate that Aph‐1 as well as NCT is not absolutely required for Notch processing, suggesting that NCT is differentially required for APP and Notch processing. In addition, our data revealed that components of the γ‐secretase complex are also important for proteasome‐ and lysosome‐dependent degradation of APP and that endogenous APP is mostly degraded by lysosome while exogenous APP is mainly degraded by proteasome. There are unanswered questions regarding the roles of each component of the γ‐secretase complex in amyloid precursor protein (APP) and Notch processing. The most relevant, novel finding of this study is that nicastrin (NCT) is required for APP but not Notch processing, while Aph‐1 is not essential for processing of both APP and Notch, suggesting NCT as a therapeutic target to restrict Aβ formation without impairing Notch signaling. Abstract : There are unanswered questions regarding the roles of each component of the γ‐secretase complex in amyloid precursor protein (APP) and Notch processing. The most relevant, novel finding of this study is that nicastrin (NCT) is required for APP but not Notch processing, while Aph‐1 is not essential for processing of both APP and Notch, suggesting NCT as a therapeutic target to restrict Aβ formation without impairing Notch signaling.